Acidic ribosomal P proteins are phosphorylated in Trypanosoma cruzi - Gomez, Eliana B. (2001)
Trypanosoma cruzi ribosomes from epimastigote forms were purified as determined by electron microscopy and isoelectrofocusing was used to analyse this purified ribosome fraction. Silver stained gels revealed that acidic proteins are present in at least 10 different isoforms, in accord with previous cloning studies. To detect phosphorylation, in vitro phosphorylation assays using the recombinant protein TcP2β-mbp were carried out. The results showed that T. cruzi cytosolic fraction possesses protein kinase activity able to phosphorylate the recombinant protein. Purified ribosomes contain protein kinases that could also phosphorylate the recombinant protein TcP2β-mbp. Labelling parasites with [32Pi] in a phosphate free medium demonstrated that ribosome proteins, recognised with a specific mouse antiserum against recombinant TcP2β proteins, are phosphorylated in vivo. All these results suggest that in vivo phosphorylation of ribosome TcP2β proteins are mediated by protein kinase(s) not yet identified.